Investigation of the optical properties of Pb1-xCdxTe films using spectroscopic ellipsometry - Kovach, Samuel; Maksimov, Oleg; Bhattacharya, Pijush; Peiris, Frank (Thin solid films, 2024)
•Single phase rock-salt Pb1-xCdxTe (0 ≤ x ≤ 0.15) films were produced.•The lattice constant of Pb1-xCdxTe decreases as a function of Cd concentration.•The band gap of Pb1-xCdxTe blue shifts as the Cd concentration increases.•The index of refraction decreased by ∼10 % as Cd increases. Using spectroscopic ellipsometry, we studied the optical properties of four Pb1-xCdxTe (0 ≤ x ≤ 0.20) films. The Pb1-xCdxTe films, deposited on silicon substrates using an electron-beam deposition technique, show a rock-salt structure, with their lattice constants decreasing as a function of Cd concentration. Ellipsometry measurements, which covered a wide spectral range between 0.1 eV to 4.1 eV, determined the index of refraction and the extinction coefficient of the films. As the Cd concentration increases from 0 % to 20 % in the Pb1-xCdxTe films, the index of refraction decreases by ∼10 %, across the entire energy range. Similarly, there seems to be a decrease in the extinction coefficient with the increase of Cd concentration. An oscillator model, depicting the optical functions of each Pb1-xCdxTe film, allowed us to obtain the band gap of each film which blue-shifts as the Cd concentration is increased. Besides the fundamental band gap, we recovered the higher-order electronic transitions that occur in the Brillouin zone of the Pb1-xCdxTe lattice.